Implementation of Cooperative Learning Method in Enhancing Collaboration and Communication of 12th-Grade Students at SMA Takhassus Al-Quran - Hufron, Ahmad; Chaerulamin, MH; Nurul Arifin, Laelatul; Ulviyana, Leni (International Journal on Education Issues, 2025)
Purpose - This study aims to analyze the effect of Kahoot application-based quisis method on students' enthusiasm in participating in Islamic Religious Education and Cultivation (PAIBP) lessons in class 12 AKL 3 SMK Bhakti Praja Adiwerna, Tegal. The Kahoot quiz method was chosen because of its ability to increase student interaction and engagement. Design/Methodology/Approach - The research method used was quantitative with an experimental design. The study population consisted of 30 students, and data was collected through a questionnaire that measured the level of student enthusiasm before and after the application of the Kahoot method. Data analysis was conducted using descriptive statistics and t-test to determine significant differences in student enthusiasm. Findings - The results showed that there was a significant increase in students' enthusiasm after the application of the Kahoot method, with the average enthusiasm score increasing from 65 before the application to 85 afterwards. This finding indicates that the use of Kahoot quiz method can be an effective alternative in increasing students' enthusiasm in EAP learning. Originality/Value - This research is expected to contribute to the development of more interesting and interactive learning methods in schools.